PENGARUH VARIASI CDI DAN PUTARAN MESIN TERHADAP DAYA MESIN PADA SEPEDA MOTOR SUZUKI SATRIA F 150 CC TAHUN 2008 - Sigit, Gama Satria (Jurnal Nosel, 2013)
The purpose of this research are: (1) To understand the effect of using various CDI to power of engine on suzuki satria F150 year 2008 motorcycle. (2) To understand the effect of various rpm to power of engine on suzuki satria F150 year 2008 motorcycle. (3) To understand the common effect (interaction) between using various CDI and various prm towards power of engine on suzuki satria F150 year 2008 motorcycle. This research was do at 26 juny 2012 and be located in workshop MOTOTECH Jl. Ringroad Selatan, Kemasan, Singosaren, Banguntapan, Bantul, Yogyakarta telp. (0274) 6536303. This type of research is experiment reseach with factorial design 3x7 and quantitative approach. The population on this sample was suzuki satria F150 year 2008 motorcycle. Sampling of this research is Suzuki Satria F150 year 2008 motorcycle with serial police number G 6161 TT and serial engine number is G420IDI67935. The sampling obtainable using purposive sampling technique. The data obtained from the power measurement of engine motrcycle using with dynotest. The data obtain with 3 times of replications, so that 63 data were obtained. Technique of data analysis in this research was two-ways analysis of variance,before implement data analysis pre especially doing prerequisite test namely normality test and homogenity test. Normality test used lilifors test and homogenity test used Bartlett test. Based on the research result, it can be concluded that: (1) There are an effect of various CDI and power of engine on suzuki satria F150 year 2008 motorcycle. This is shown by the results of data analysis, that Fobs = 50,691 greater than Ftabel = 5,149 level of significance (?)  at 1%. (2) There are an effect of rpm to power of engine on suzuki satria F150 year 2008 motorcycle. This is shown by the results of data analysis, that Fobs = 329,0331 greater than Ftabel = 3,266 level of significance (?)  at 1%. (3) There aren?t an effect of various CDI and various rpm to power of engine on suzuki satria F150 year 2008 motorcycle. This is shown by the results of data analysis, that Fobs= 0,383 smaller than Ftabel = 2,640 level of significance (?)  at 1%. (4) Maximum power of engine is 16,2 Hp obtained from using CDI dual band curva 2 with 9242 RPM.